2012
DOI: 10.1007/s12291-012-0219-6
|View full text |Cite
|
Sign up to set email alerts
|

Does HCV Patients Who Have BCL2 43Ala Genotype and Normal GH1 Levels Can Achieve Response to IFN Based Therapy?

Abstract: The main objective of the current study is to examine the role of the statistical relation between BCL2 gene (Ala43Thr) single nucleotide polymorphism and growth hormone (GH1) levels in Egyptian HCV genotype-4 patients before and after treatment with pegylated interferon plus ribavirin. Eighty patients with HCV genotype-4 and 40 healthy volunteers as controls were enrolled in the prospective study. Gene polymorphism of BCL2 (Ala43Thr) using PCR-RFLP technique and GH1 concentrations using ELISA procedure were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We compared the statistical relationship between the BCL2 gene (Ala43Thr) single-nucleotide polymorphism and growth hormone (GH1) levels in Egyptian HCV genotype-4 patients, both before and after treatment with PEG IFN plus ribavirin. The results showed that patients with HCV genotype-4 with normal GH1 concentration and the BCL-2/43Ala genotype could successfully achieve a response to IFN therapy [51]. We undertook to investigate the expression and relationship of the HCV core proteins -P21 and Bcl-2in tissues of patients with hepatitis C and cirrhosis; the positive expression of HCV core protein and mutant P21 is mainly located in the nucleus; for Bcl-2, the positive expression was mainly located in the cytoplasm; furthermore, the positive expression rate of P21 was only 13%, and the positive expression rate of Bcl-2 was 95.7%.…”
Section: Discussionmentioning
confidence: 98%
“…We compared the statistical relationship between the BCL2 gene (Ala43Thr) single-nucleotide polymorphism and growth hormone (GH1) levels in Egyptian HCV genotype-4 patients, both before and after treatment with PEG IFN plus ribavirin. The results showed that patients with HCV genotype-4 with normal GH1 concentration and the BCL-2/43Ala genotype could successfully achieve a response to IFN therapy [51]. We undertook to investigate the expression and relationship of the HCV core proteins -P21 and Bcl-2in tissues of patients with hepatitis C and cirrhosis; the positive expression of HCV core protein and mutant P21 is mainly located in the nucleus; for Bcl-2, the positive expression was mainly located in the cytoplasm; furthermore, the positive expression rate of P21 was only 13%, and the positive expression rate of Bcl-2 was 95.7%.…”
Section: Discussionmentioning
confidence: 98%
“…Intriguingly, it was found that HCV genotype-4 patients who have normal growth hormone concentrations and BCL2 43Ala genotype can successfully achieve response to interferon-based therapy. 61 In addition, the hormonal profile (prolactin, total testosterone, growth hormone) provides promising biomarkers for HCV treatment response when associated with P53 rs1042522 and CD95 rs1800682 genetic polymorphisms; where sustained virological responders have low prolactin levels and either P53 rs1042522 C/C genotype or CD95 rs1800682 A/A genotype, high total testosterone concentrations and P53 rs1042522 C/C genotype, as well as high growth hormone levels and either P53 rs1042522 G/G genotype or CD95 rs1800682 A/A genotype compared to non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…Another very important factor which is powerfully involved as a pre-treatment predictor is the host gene. Various genetic polymorphisms of IL28B [18,19], 2 0 -5 0 -OAS [20], and BCL2 [21][22][23] were examined previously with the HCV response to the IFN-based therapy. These genetic polymorphisms provided good examples of pre-therapeutic host gene predictors for interferon response.…”
Section: Introductionmentioning
confidence: 99%